Answer:
p = 13, q = 9
Explanation:
Given the 2 equations
-
=
( multiply through by 6 to clear the fractions )
3q - 2p = 1 → (1)
-
= 5 ( multiply through by 6 to clear the fractions )
3p - q = 30 , that is
- q + 3p = 30 → (2)
Multiplying (2) by 3 and adding to (1) eliminates the term in q
- 3q + 9p = 90 → (3)
Add (1) and (3) term by term to eliminate q
7p = 91 ( divide both sides by 7 )
p = 13
Substitute p = 13 into (2) for corresponding value of q
- q + 3(13) = 30
- q + 39 = 30 ( subtract 39 from both sides )
- q = - 9 ( multiply both sides by - 1 )
q = 9
Thus p = 13 and q = 9